Deconvolution of electrochemical impedance data for the monitoring of electrode degradation in VRFB. (10th March 2020) - Schneider, Jonathan; Tichter, Tim; Khadke, Prashant; Zeis, Roswitha; Roth, Christina
Abstract: Understanding degradation phenomena occurring during the operation of vanadium redox-flow batteries (VRFB) requires a measurement technique which allows for differentiating the overall performance losses into individual performance losses of the cell components. For this purpose, electrochemical impedance spectroscopy (EIS) is a valuable and well established tool. However, the discrimination of processes taking place at similar time scales is challenging since they overlap in the commonly used Nyquist or Bode representation. Distribution of relaxation times (DRT) analysis tackles this issue by deconvoluting EIS data with respect to the time constants of the individual processes. It hence circumvents the necessity of finding a suitable equivalent circuit model and thus allows for data evaluation without any a-priori knowledge of the system under study. For the first time, we herein present the application of DRT transform to EIS data of a VRFB. By varying experimental conditions and employing full cell as well as double half cell operational modes, we are able to identify the faradaic process of the negative half cell. This enables us to visualize the negative half cell's contribution to the overall impedance of a VRFB even in a full cell EIS measurement. By an accelerated degradation experiment we finally demonstrate the great potential of DRT analysis for future application in the monitoring of electrode degradation in VRFB.